EFFECT OF CARROT JUICE (DAUCUS CAROTA ) ON MITOTIC INDEX AND FORMATION OF MICRONUCLEI IN FEMUR BONE MARROW CELLS OF WHITE MICE - Ilham A. Khalaf (Mesopotamia Journal of Agriculture)
The effect of carrot juice at different doses on mitotic index (MI)and micronuclei (Mn) formation was studied in white mice bone marrow cells . The counter effect of juice was also studied against the effects induced by cyclophosphamide (Cp) . Results indicated that carrot juice (0.1 , 0.25 , 0.5 ) ml administered orally had no effect on MI and formation of micronuclei , while Cp (50 mg / Kg body weight ) lowered the MI from 6.34 (The normal level ) to 1.97 after 24 hr , and increased the micronuclei from the normal level (1.48) to 13.06 . Different combinations of juice and mutagen such as using juice before mutagen (Ca/Cp) , or juice after mutagen (Cp/Ca) and using juice with mutagen (Ca+Cp) , had different effects , all of them were able to restore the MI to the natural values especially after 6 days . The level of Mn remained elevated compared to the natural values especially in using Cp/Ca and Ca+Cp treatments .